2012
DOI: 10.2174/092986712803306394
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies Against Prostate Cancer – Pt(II)-Based Chemotherapy

Abstract: Prostate cancer is the second most common cancer worldwide and the sixth cause of cancer-related death in men. When hormone therapy fails to control tumour growth, castration-resistant prostate cancer (CRPC) occurs and chemotherapy drugs must be administered. Since 2004, docetaxel administration is the standard of care in metastatic CRPC, although it presents severe limitations such as acquired resistance and poor prognosis. An analogue (cabazitaxel) was approved by the FDA in 2010 as a second-line chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 100 publications
(124 reference statements)
0
14
0
Order By: Relevance
“…Biologic chemotherapeutics which inhibit a single specific pathway and are effective in the short term are often not effective to treat cancer in the long term due to development of drug resistance and robust relapse ( 26 29 ). Up-regulation of DNA repair pathways is one way in which tumor cells become resistant to therapy and through which mitotic catastrophe is avoided in damaged tumor cells ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biologic chemotherapeutics which inhibit a single specific pathway and are effective in the short term are often not effective to treat cancer in the long term due to development of drug resistance and robust relapse ( 26 29 ). Up-regulation of DNA repair pathways is one way in which tumor cells become resistant to therapy and through which mitotic catastrophe is avoided in damaged tumor cells ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The largest of these studies found a PSA response rate of 34.5 % in 80 patients given 50 mg/m 2 of oral cyclophosphamide daily with a mediation response duration of 7.5 months. Carboplatin at 150 mg/m 2 weekly was evaluated in 27 patients with minimal effects (26.9 % of patients had a PSA that declined, but none of the response were >50 % decline) [65]. A study in the early 1990s in 25 patients demonstrated a 17 % partial response rate in evaluable patients and a 20 % PSA response rate [66].…”
Section: Non-taxane Chemotherapeuticsmentioning
confidence: 99%
“…Chemotherapy is one of the primary treatment methods used in prostate cancer patients (7)(8)(9). Cisplatin (chemical structure shown in Fig.…”
Section: Introductionmentioning
confidence: 99%